Correction: Liu et al. Selenoprotein M Inhibits the Replication of Influenza A Virus by Regulating Reactive Oxygen Species Levels. Life 2025, 15, 714 - Minxuan Liu; Jinhui Wang; Weigang Li; Bo Zhao; Yuanyuan Zhang; Qiaoying Zeng; Guangyuan Liu (Life, 2025)
In the original publication [...]